2014
DOI: 10.4149/av_2014_03_278
|View full text |Cite
|
Sign up to set email alerts
|

Significance of mutations in hepatitis B virus X gene for the pathogenesis of HB-associated glomerulonephritis

Abstract: In this study, the significance of hepatitis B virus (HBV) X gene mutations for the pathogenesis of HBV-associated glomerulonephritis (HBV-GN) was investigated. DNA was extracted from 50 HBV-GN patients and 60 asymptomatic HBV carriers and subjected to PCR amplification and sequencing of HBV X gene. In HBV-GN patients, missense nucleotide mutations of C1653T,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In addition, acquired missense nucleotide mutations of the HBV x gene in specific locations (C1653T, A1726C, A1727T, C1730G, T1753C, A1762T, and G1764A) were found in 84% of patients with MN and in only 8% of control patients, which may explain the predisposition of certain HBV carriers to develop renal disease (10). Of the eight genotypes of HBV, genotype A appears to have the highest risk of MN or MPGN.…”
Section: Membranous Nephropathymentioning
confidence: 97%
“…In addition, acquired missense nucleotide mutations of the HBV x gene in specific locations (C1653T, A1726C, A1727T, C1730G, T1753C, A1762T, and G1764A) were found in 84% of patients with MN and in only 8% of control patients, which may explain the predisposition of certain HBV carriers to develop renal disease (10). Of the eight genotypes of HBV, genotype A appears to have the highest risk of MN or MPGN.…”
Section: Membranous Nephropathymentioning
confidence: 97%
“…We have mentioned the possible relationship between different genotypes of HBV and associated nephropathy. Further studies have found that mutations in HBV genes (C1653T, A1726C, A1727T, C1730G, T1753C, A1762T, and G1764A) are present in 84% of patients with membranous nephropathy (21).…”
Section: Host and Viral Genetic Factorsmentioning
confidence: 99%
“…HBx as a multifunctional protein encoded by HBV can modulate multiple signaling pathways such as HBV replication, cellular transcription, cell cycle, DNA repair, etc ( Lei et al, 2019 ; Yang et al, 2018 ). Past studies have shown that mutations at key genetic loci plays an important role in HBV-GN progression ( Hui et al, 2014 ). HBx overexpression could decrease cell viability of podocytes and cause increased podocyte injury ( Lei et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%